The Influence of CRM (Customer Relationship Management) and Company Image on Customer Satisfaction and Loyalty at PT. Bank Rakyat Indonesia (Persero) Tbk Tambun Branch Office - Bekasi - Fauzobihi, Fauzobihi; Yusuf, Asep Ramadhani; Partimah, Partimah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Indonesian people's banks have a good reputation, such as BRI, have a high level of trust, a high level of performance, and have good business ethics. BRI also has a good personality, such as always being responsible to customers, having good achievements, having good social responsibility, and having customers with a high level of trust in Bank Rakyat Indonesia. This also makes customers loyal to do business with BRI.Discussion of the Customer Relationship Management variable (X1) and the Company Image variable (X2) on Satisfaction (Y1).a. The Influence of Customer Relationship Management (CRM) on Satisfaction.H0: b1= 0 CRM has no significant effect on customer satisfaction.H1:b1≠ 0 CRM has a significant effect on customer satisfaction.In the t test results, the Customer Relationship Management variable (X1) and the Satisfaction variable (Y1) show a significance value of 0.000 < 0.05. So it can be concluded that there is a significant influence between customer relationship management variables on satisfaction.b. The Influence of Company Image on Satisfaction.H0: b1= 0 Company image has no significant effect on customer satisfaction.H1:b1≠ 0 Company image has a significant effect on customer satisfaction.In the t test results, the Company Image variable (X2) against the Satisfaction variable (Y1) shows a significance value of 0.000 < 0.05. So it can be concluded that there is a significant influence between the company image variables on satisfaction.Discussion of the Customer Relationship Management variable (X1) and the Company Image variable (X2) on Loyalty (Y2).a. The Influence of Customer Relationship Management (CRM) on Loyalty.H0: b1= 0 CRM has no significant effect on customer loyalty.H1:b1≠ 0 CRM has a significant effect on customer loyalty.In the t test results, the Customer Relationship Management variable (X1) and the Loyalty variable (Y2) show a significance value of 0.000 < 0.05. So it can be concluded that there is a significant influence between customer relationship management variables on loyalty.b. The Influence of Company Image on Loyalty.H0: b1= 0 Company image has no significant effect on customer loyalty.H1:b1≠ 0 Company image has a significant effect on customer loyalty.In the t test results, the Company Image variable (X2) against the Loyalty variable (Y2) shows a significance value of 0.001 < 0.05. So it can be concluded that there is a significant influence between the company image variables on loyalty.